2009
DOI: 10.1016/j.jvs.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Vascular surgery training trends from 2001-2007: A substantial increase in total procedure volume is driven by escalating endovascular procedure volume and stable open procedure volume

Abstract: Vascular surgery trainees are performing a vastly increased total number of procedures. This increase in total procedure volume is almost entirely attributable to the recent increase in endovascular procedures. Aside from a small decline in open aortic procedures, the volume of open surgical procedures has largely remained stable. It is essential that vascular surgery training programs continue to focus on both endovascular and open surgical skills in order for vascular surgeons to remain the premier specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 17 publications
1
60
0
1
Order By: Relevance
“…7,17 These findings are attributable to the increased prevalence of vascular disease in the general, aging population and to the current endovascular treatment options for patients who were previously not candidates for OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,17 These findings are attributable to the increased prevalence of vascular disease in the general, aging population and to the current endovascular treatment options for patients who were previously not candidates for OS.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of ES on decreasing OS volume was most evident in this group. Interestingly, Schanzer et al 17 found that the overall volume of carotid endarterectomies was not affected by endovascular procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The number of open aneurysms seen by vascular surgical residents and fellows during their training is markedly decreased from what it once was. While vascular volumes for trainees are rising overall, this increase is predominantly comprised of endovascular cases [27]. It is projected that by 2020, the average vascular surgical trainee will have performed only five open surgical aortic aneurysm repairs [5].…”
Section: Effect Of Trends On Training Of Vascular Surgeonsmentioning
confidence: 99%
“…Such need is driven by evidence that skill level can affect clinical outcomes after surgery (Reznick & MacRae, 2006). Assessment is often done informally through subjective feedback from other surgeons (Chaer et al, 2006;Bech et al, 2011;Riga et al, 2011) or based on a simple count of the number of times a procedure has been performed (Cronenwett, 2006;Schanzer et al, 2009). …”
mentioning
confidence: 99%